Digital Transformation in Food Supply Chains in Central and Eastern Europe - Szegedi, Zoltan; Ulechla, Gergely; Miskolczi-Gabriel, Monika (International Journal of Economics, Business and Management Studies, 2022)
The phenomena of technology and digitalization have developed rapidly most recently, leaving traces in all branches of industry. With the prevalence of Industry 4.0 and with digitalization being on the rise, companies have expanded more and more successfully. Thus, in addition to global supply chains, their own supply chains have also started to develop considerably. The aim of our research is to discover the factors characterizing the digital transformation of companies in the Central and Eastern European region. This article assesses the conditions, key drivers, and barriers of digital transformation and the benefits expected by companies operating in the agricultural and food supply chains. The research is based on a questionnaire survey of over hundred companies. From the answers, models were created to each group of questions by using factor analysis. The results show that the most important motivating factors are quality improvement, market pull, and technological push impacts. The barriers identified are largely consistent with those reported in the contemporary literature. Companies expect benefits mostly from “sales and customer relations”, followed by “logistics and marketing”, and “production and sourcing”.